An ecologically oriented conceptual model of vocational rehabilitation of people with acquired midcareer disabilities - Dobren, Arlene A. [Verfasser] (My University, 1994)
"The author considers the vocational rehabilitation of addults who acquire disabilities during their midcareer years. A review of the literature reveals that neither traditional theories of vocational development nor those designed specifically for the rehabilitation of individuals with midcareer disabilities provide a comprehensive framework for understanding the vocational behavior of this population. Although recent theoretical advances in both field have paralleled each other, there is scant recognition of this. The author uncovers one overlapping area - human ecology - and, from this develops a model designed to facilitate the rehabilitation of individuals with midcareer disabilities. Implications for practice and research are discusses." (author's abstract, IAB-Doku) ((en)) Die Autorin stellt fest, dass bisher weder in den traditionellen Theorien der beruflichen Entwicklung noch in speziellen Theorien der beruflichen Rehabilitation die Situation von Personen, deren Behinderung im mittleren Erwerbsleben auftritt, ausreichend berücksichtigt wird. Sie entwickelt deshalb ein ökologisch orientiertes Modell der beruflichen Rehabilitation für diesen Personenkreis. (IAB)
Ein ökologisch orientiertes Konzept der beruflichen Rehabilitation von Menschen, bei denen in der Mitte des Erwerbslebens eine Behinderung auftritt
Keywords: G 1.3.3.4 Wiedereingliederung; G 2.3.1 Arbeitsteilung & -organisation; P 1 Zielgruppen; Berufliche Rehabilitation; Modell; Menschen mit Behinderung; Mittleres Lebensalter